Infective endocarditis complicating transcatheter aortic valve implantation. Issue 7 (13th January 2020) - Harding, Daniel; Cahill, Thomas J; Redwood, Simon R; Prendergast, Bernard D
Abstract : Infective endocarditis complicating transcatheter aortic valve implantation (TAVI-IE) is a relatively rare condition with an incidence of 0.2%–3.1% at 1 year post implant. It is frequently caused by Enterococci, Staphylococcus aureus and c oagulase negative staphylococci . While the incidence currently appears to be falling, the absolute number of cases is likely to rise substantially as TAVI expands into low risk populations following the publication of the PARTNER 3 and Evolut Low Risk trials. Important risk factors for the development of TAVI-IE include a younger age at implant and significant residual aortic regurgitation. The echocardiographic diagnosis of TAVI-IE can be challenging, and the role of supplementary imaging techniques including multislice computed tomography (MSCT) and positron emission tomography ( 18 FDG PET) is still emerging. Treatment largely parallels that of conventional prosthetic valve endocarditis (PVE), with prolonged intravenous antibiotic therapy and consideration of surgical intervention forming the cornerstones of management. The precise role and timing of cardiac surgery in TAVI-IE is yet to be defined, with a lack of clear evidence to help identify which patients should be offered surgical intervention. Minimising unnecessary healthcare interventions (both during and after TAVI) and utilising appropriate antibiotic prophylaxis may have a role in preventing TAVI-IE, but robust evidence for specific preventative strategies is lacking. Further research is required to better select patients for advanced hybrid imaging, to guide surgical management and to inform prevention in this challenging patient cohort.